PERUNDUNGAN SIBER (CYBERBULLYING) BERMUATAN PENISTAAN AGAMA DI MEDIA SOSIAL YANG BERDAMPAK HUKUM: KAJIAN LINGUISTIK FORENSIK - Agus Syahid; Dadang Sudana; Andika Dutha Bachari (Jurnal Semantik, 2022)
Recently in Indonesia, there have been many cyberbullying containing blasphemy on social media such as what was done by Joseph Paul Zhang and M. Kece. Of course, it can cause legal implications if there are other peoples who feel humiliated. This research aims to (1) analyze illocutionary speech acts of cyberbullying containing blasphemy on social media, (2) reveal the legal impact of the utterance cyberbullying containing blasphemy, and (3) determine the characteristics of cyberbullying containing blasphemy. The method of this research is qualitative with forensic linguistic approach. The data of the research were collected from the copies of court verdict. Based on the analysis, the illocutionary speech act by defendants includes; expressive (hate speech, humiliation), directive (insulting), and assertive (lies). The legal impact of cyberbullying containing blasphemy carried out by the defendants on social media can be charged based on the Law of the Republic Indonesian Article 28 paragraph (2) Law Number 19 of  2016 about Information and Electronic Transactions (the ITE Law). The characteristic of cyberbullying containing blasphemy on social media is the use of harsh words, insults, and blasphemy against religious group, God, Prophets, the holy scriptures/verse, and other religious symbols.